2008
DOI: 10.1017/s0022029907003032
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-High Pressure Homogenization-Induced Changes in Skim Milk: Impact on Acid Coagulation Properties

Abstract: The effects of ultra-high pressure homogenization (UHPH) on skim milk yogurt making properties were investigated. UHPH-treated milk was compared with conventionally homogenised (15 MPa) heat-treated skim milk (90 degrees C for 90 s), and to skim milk treated under the same thermal conditions but fortified with 3% skim milk powder. Results of the present study showed that UHPH is capable of reducing skim milk particle size which leads to the formation of finer dispersions than those obtained by conventional hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
2
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 22 publications
5
21
2
5
Order By: Relevance
“…Weak gels have a strong tendency to flow (Pereira et al, 2003); they are also more prone to shrinkage and subsequent expulsion of whey (Serra, Trujillo, Jaramillo, Guamis, & Ferragut, 2008). These findings were generally in agreement with the results of the study of Serra, Trujillo, Quevedo, Guamis, and Ferragut (2007) on yoghurt produced from HPH-treated (100-300 MPa) skim milk.…”
Section: Non-fat Yoghurtsupporting
confidence: 90%
“…Weak gels have a strong tendency to flow (Pereira et al, 2003); they are also more prone to shrinkage and subsequent expulsion of whey (Serra, Trujillo, Jaramillo, Guamis, & Ferragut, 2008). These findings were generally in agreement with the results of the study of Serra, Trujillo, Quevedo, Guamis, and Ferragut (2007) on yoghurt produced from HPH-treated (100-300 MPa) skim milk.…”
Section: Non-fat Yoghurtsupporting
confidence: 90%
“…HPH is an innovative method in yogurt processing which improves the coagulation characteristics of milk due to making the balance between soluble and insoluble forms of nitrogen, calcium and phosphorus, therefore more desirable yogurt is produced [34]- [36] Additionally, HPH treatment improves the rheological properties such as viscosity, firmness and syneresis resistance of gels [7], [28], increases the viability of L. delbrueckii and S. thermophilus during storage of yogurt in refrigerator and decreases the risks of post-acidification [37], [38]. Increasing viscosity index and gel firmness with pressure can be illustrated with the casein-fat or casein-casein interactions and the denatured whey proteins binding with water and fat which are caused by HPH treatment [34], [39], [40].…”
Section: Effect On Yogurt Propertiesmentioning
confidence: 99%
“…Such ingredients are generally added at levels of 3 or 4%, raising the total solids level to 14-15%, thus increasing the production costs (Amatayakul et al, 2006). Ultra-high pressure homogenization (UHPH) is a promising technology, based on the same principle as conventional homogenization, but working at significantly higher pressures, which is currently being investigated for the manufacture of yoghurt (Serra et al, 2009(Serra et al, , 2008(Serra et al, , 2007. In a previous study (Serra et al, 2007) UHPH samples were compared with heat-treated milk both with and without skim milk powder (SMP) added, and it was concluded that yoghurts made from milk UHPH-treated at 200 or 300 MPa had higher gel firmness, less syneresis and lower titratable acidity than those obtained from conventionally treated milk with SMP.…”
Section: Introductionmentioning
confidence: 99%